Anesthesia advances in ASCs. Issue 5 (27th September 2015) - Neft, Michael W.
<x xml:space="preserve">Abstract</x> Anesthesia is 50 times safer today than it was in the 1980s. With superior monitoring devices and ultra-short-acting agents, anesthesia care can be tailored to almost any patient population and its needs.